2022
DOI: 10.3390/life12040602
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Genetic Polymorphisms in Glutamate-Cysteine Ligase, a Key Enzyme of Glutathione Biosynthesis, on Ischemic Stroke Risk and Brain Infarct Size

Abstract: The purpose of this pilot study was to explore whether polymorphisms in genes encoding the catalytic (GCLC) and modifier (GCLM) subunits of glutamate-cysteine ligase, a rate-limiting enzyme in glutathione synthesis, play a role in the development of ischemic stroke (IS) and the extent of brain damage. A total of 1288 unrelated Russians, including 600 IS patients and 688 age- and sex-matched healthy subjects, were enrolled for the study. Nine common single nucleotide polymorphisms (SNPs) of the GCLC and GCLM ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 122 publications
0
10
0
Order By: Relevance
“…The previous studies have already revealed genetic markers associated with the development of IS [6,7,8], as well as related phenotypes/risk factors, such as hypertension [9,10,11], atherosclerosis [12,13], and thrombosis [14]. However, despite the large number of studies conducted in the world, the molecular mechanisms of IS development remain poorly understood.…”
mentioning
confidence: 99%
“…The previous studies have already revealed genetic markers associated with the development of IS [6,7,8], as well as related phenotypes/risk factors, such as hypertension [9,10,11], atherosclerosis [12,13], and thrombosis [14]. However, despite the large number of studies conducted in the world, the molecular mechanisms of IS development remain poorly understood.…”
mentioning
confidence: 99%
“…GSH is synthesized in two steps that are catalyzed, successively, by two polymorphic enzymes: γ-glutamylcysteine synthetase (glutamate-cysteine ligase, GCL) and GSH synthetase. GCL is the rate-limiting enzyme in glutathione biosynthesis and genetic polymorphisms in its catalytic (GCLC) and modifying (GCLM) subunits were associated with increased susceptibility to oxidative stress and with increased MI risk in the general population and T2D patients [ 96 ]. Although no associations with either GCLC or GCLM polymorphisms as stand-alone risk factors for T2DM complications were observed within Slovenian T2DM patients [ 40 ], in Japanese patients, GCLM C-588T polymorphism was included in the composite 5 polymorphic gene score associated with increased risk for CHD [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms of glutamate cysteine ligase that are correlated with a decrease in GCLC mRNA and protein expression, enzyme activity, and GSH content [ 47 , 48 , 49 , 50 , 51 ] represent attractive markers for studying the molecular mechanisms of psoriasis. Polymorphisms of the GCLC gene have been found to be associated with the risk of cardiometabolic diseases such as coronary artery disease [ 52 , 53 ], ischemic stroke [ 54 ], type 1 [ 55 , 56 ] and type 2 [ 51 ] diabetes mellitus, polycystic ovary syndrome [ 57 ], and nonalcoholic fatty liver disease [ 58 ], as well as other multifactorial disorders such as bronchial asthma [ 59 ], pulmonary tuberculosis [ 60 ], and colorectal cancer [ 61 ]. However, no studies have been designed so far to investigate the role of GCLC gene polymorphisms in psoriasis susceptibility.…”
Section: Discussionmentioning
confidence: 99%